The Power of Communication and Dialogue in the Negotiation Process of the Modern Polish Police - Przybył, Justyna (Global Prosperity, 2026)
Abstract. The aim of the study is to theoretically generalize and practically substantiate the role of communication and dialogue in the negotiation process of the modern Polish police as a determining factor in de-escalating conflicts, saving lives, increasing the effectiveness of police response and strengthening public trust. The object of the study is the negotiation process in the activities of the modern Polish police as a component of professional law enforcement practice, within which communication and dialogue are the main means of influence, resolving crisis situations and ensuring public safety. The article examines the importance of communication and dialogue in the negotiation process of the modern Polish police as one of the leading components of effective law enforcement activities in the context of growing social tension, the complexity of the security environment and the increasing requirements for the humanity of police response. It is substantiated that the negotiation process in modern police practice goes far beyond the limits of narrowly operational communication in crisis situations and appears as a systemic form of professional interaction aimed at de-escalating the conflict, reducing psychological tension, building trust, preventing the use of force and achieving a safe resolution of the incident. Particular attention is focused on the fact that communication in the activities of the Polish police performs not only an informational, but also a psychological, preventive, coordination and legitimizing function, since it ensures contact with a person in a crisis situation, assesses his intentions, corrects his behavior and creates conditions for a peaceful conclusion of the event. It is proven that dialogue in the negotiation process is an indicator of the professional maturity of the modern police, as it allows achieving results without excessive escalation, maintaining a balance between the protection of public order and respect for human rights, and strengthening public trust in state authorities. At the same time, it is established that modern Polish police practice is increasingly focused on the development of specialized negotiation training, interdepartmental coordination, anti-conflict approaches and international professional interaction, which makes it possible to consider communication as a strategic resource for the modernization of the police service. Therefore, it is concluded that the strength of communication and dialogue in the negotiation process of the modern Polish police determines not only the effectiveness of individual operations, but also the overall level of humanity, legitimacy and social effectiveness of law enforcement activities.